Pengaruh Sudut Drive Pulley dan Massa Roller terhadap Daya dan Tingkat Kebisingan pada Sepeda Motor Bertransmisi Otomatis 110cc - Bagus Irawan; Purwoko Purwoko; Ratna Monasari; Ahmad Hanif Firdaus (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Automatic transmission motorcycles, especially those with 110cc engines, are increasingly in demand by the public because of their practicality. The performance of this motorcycle is greatly influenced by the transmission system, especially the Drive pulley and Roller components. The correct setting of the Drive pulley angle and Roller mass can improve engine performance and reduce noise, thus supporting driving comfort. This study aims to analyze the effect of variations in the Drive pulley angle and Roller mass on engine performance, in terms of power (HP), torque (Nm), and noise level (dB) at several engine speeds. The variations tested include the Drive pulley angle of 13.5°–14° and the Roller mass of 13–15 grams, with testing at 5000, 6000, 7000, and 8000 RPM. The test results show that the combination of the angle and Roller mass affects engine performance. At 5000 RPM, the combination of the 14° angle and 15 gram Roller produces the highest power, torque, and noise. At 6000 RPM, the combination of 13.8° and 13 grams produces a maximum power of 6.86 HP and 8.15 Nm of torque, with a noise of 97.40 dB. While at 7000–8000 RPM, the combination of 13.5° and 15 grams provides the best performance with 7.10 HP and 6.30 Nm of torque, accompanied by a noise of 104.17 dB. In general, increasing the angle and mass of the Roller increases performance, but is followed by an increase in noise.